Determinants of Educated Unemployment in Java from 2016 to 2022 - Rahmawati, Firnanda Novita; Pratomo, Devanto Shasta; Pudjihardjo, M. (Journal of International Conference Proceedings, 2023)
Statistical survey data of each province in Java indicates that the number of educated unemployed individuals holding a high school or university diploma is higher than that of lower-educated unemployed individuals. The increase in the number of educated unemployed individuals suggests that the government has not been successful in increasing job opportunities and establishing an effective education system to compete in the workforce. A significant increase happened in 2020 due to Covid-19 pandemic, leading to numerous dismissals. This research aims to discover the factors influencing educated unemployment in Java using Fixed Effect Model (FEM) panel data analysis, which comprises cross-sectional data from six provinces in Java and time series data spanning from 2016 to 2022. The results of the research show that education level variable (average years of schooling) has a negative and insignificant influence on educated unemployment, provincial minimum wage has a negative and significant influence on educated unemployment, GRDP has a positive and insignificant influence on educated unemployment, foreign direct investment has a positive and significant effect on educated unemployment, local direct investment has a positive and significant influence on educated unemployment, and Covid-19 pandemic has a positive and significant influence on educated unemployment in Java from 2016 to 2022.